Recombinant interferon-γ lentivirus co-infection inhibits adenovirus replication ex vivo. - Ling Zhang; Sen Yin; Wanlong Tan; Dong Xiao; Yunceng Weng; Wenjing Wang; Tingting Li; Junwen Shi; Lifang Shuai; Hongwei Li; Jianhua Zhou; Jean-Pierre Allain; et al. (PLoS ONE, 2012)
Recombinant interferon-γ (IFNγ) production in cultured lentivirus (LV) was explored for inhibition of target virus in cells co-infected with adenovirus type 5 (Ad5). The ability of three different promoters of CMV, EF1α and Ubiquitin initiating the enhanced green fluorescence protein (GFP) activities within lentiviruses was systematically assessed in various cell lines, which showed that certain cell lines selected the most favorable promoter driving a high level of transgenic expression. Recombinant IFNγ lentivirus carrying CMV promoter (LV-CMV-IFNγ) was generated to co-infect 293A cells with a viral surrogate of recombinant GFP Ad5 in parallel with LV-CMV-GFP control. The best morphologic conditions were observed from the two lentiviruses co-infected cells, while single adenovirus infected cells underwent clear pathologic changes. Viral load of adenoviruses from LV-CMV-IFNγ or LV-CMV-GFP co-infected cell cultures was significantly lower than that from adenovirus alone infected cells (P=0.005-0.041), and the reduction of adenoviral load in the co-infected cells was 86% and 61%, respectively. Ad5 viral load from LV-CMV-IFNγ co-infected cells was significantly lower than that from LV-CMV-GFP co-infection (P=0.032), which suggested that IFNγ rather than GFP could further enhance the inhibition of Ad5 replication in the recombinant lentivirus co-infected cells. The results suggest that LV-CMV-IFNγ co-infection could significantly inhibit the target virus replication and might be a potential approach for alternative therapy of severe viral diseases.